Research trends among new investigators at ISOQOL: a bibliometric analysis from 2019 to 2023 - Kwon, Jae-Yung; Kaur, Manraj N.; Elsman, Ellen B. M.; Mehdipour, Ava; Lo, Lori Suet Hang; Ahmed Osman, Ahmed Mohamed Yehia Naguib; Herbelet, Sandrine; Ng, Carrie-Anne; van der Weijst, Lotte (Springer Nature, 2025)
Background New investigators (NI), encompassing graduate students, recent doctoral graduates, and early-career faculty, are instrumental in advancing quality of life (QoL) research through innovative methodologies and diverse perspectives. Within the International Society for Quality of Life Research (ISOQOL), the New Investigators Special Interest Group (NI-SIG) fosters collaboration and supports this community. This study utilizes bibliometric analysis to examine the contributions of NI-SIG members, focusing on publication trends, collaboration patterns, and thematic developments in QoL research.